YOUR LANGUAGE OR MINE? THE NONCOMMUNICATIVE BENEFITS OF LANGUAGE SKILLS. (18th December 2017) - Caminal, Ramon; Di Paolo, Antonio
Abstract : Do languages matter beyond their communicative benefits? We explore the potential role of preferences over the language of use, theoretically and empirically. We focus on Catalonia, a bilingual society where everyone is fully proficient in Spanish, to isolate linguistic preferences from communicative benefits. Moreover, we exploit the language‐in‐education reform of 1983 to identify the causal effects of language skills. Results indicate that the policy change has improved the Catalan proficiency of native Spanish speakers, which in turn increased their propensity to find Catalan‐speaking partners. Hence, the acquisition of apparently redundant language skills has reduced endogamy. ( JEL C26, C78, I28, J12, J15, Z13)